A Visual Transformation: Using Photography to Boost Tugu Jawa's Brand Visibility - Rafiqi, Hindam Basith; Kusumawati, Yudhistya Ayu; Widita, Anindya (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2024)
The MSMEs sector is able to contribute to economic growth in Indonesia. Jawa Sehati Mulia is an MSMEs which operates in the field of producing soy sauce made from local black soybeans with several product variants including sweet soy sauce, spicy soy sauce, barbeque soy sauce, etc. This research explores the impact of photography as a key tool in enhancing brand identity and increasing visibility for Tugu Jawa, a traditional Indonesian local brand. In an increasingly visual world, effective imagery has become essential in distinguishing brands in competitive markets. Tugu Jawa, known for its rich cultural heritage and artisanal products, has the potential to expand its reach by adopting a modern, visually appealing photography strategy. This study aims to analyze how high-quality, culturally resonant photography can effectively communicate the brand’s values, evoke emotional connections, and create a memorable presence across digital and print media. Through a series of case studies, visual analysis, and consumer feedback, the research investigates how curated imagery can elevate brand perception, improve engagement, and drive consumer interest. The findings suggest that a well-defined visual approach using photography can significantly enhance Tugu Jawa’s market visibility, attract a wider audience, and strengthen its connection with both local and global consumers. Ultimately, this study provides actionable recommendations for Tugu Jawa to leverage photography as a strategic tool to boost brand awareness and foster long-term brand loyalty.